Card art : create treasured greetings from fabric & paper - Terry, Susan S. (Susan Spangenberg), 1941- (Lafayette, Calif. : C&T Pub., 2006)
Over 50 original card designs and a dozen gift tags. Great for scrappers, quilters and anyone who loves to create keepsakes.
Includes bibliographical references (p. 79) and index.
Keywords: Greeting cards; Textile crafts